2017
DOI: 10.1039/c7md00311k
|View full text |Cite
|
Sign up to set email alerts
|

MAO inhibitory activity of bromo-2-phenylbenzofurans: synthesis, in vitro study, and docking calculations

Abstract: Monoamine oxidase (MAO) is an enzyme responsible for metabolism of monoamine neurotransmitters which play an important role in brain development and function. This enzyme exists in two isoforms, and it has been demonstrated that MAO-B activity, but not MAO-A activity, increases with aging. MAO inhibitors show clinical value because besides the monoamine level regulation they reduce the formation of by-products of the MAO catalytic cycle, which are toxic to the brain. A series of 2-phenylbenzofuran derivatives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…In another study on benzofurans, Delogu et al designed a library of 2‐phenylbenzofuran derivatives ( 9a ‐ l ) by introducing a bromine substituent in the 2‐phenyl ring and a methyl group at the positions 5 to 7 in the benzofuran moiety (Figure ). Most of compounds preferentially inhibited hMAO‐B in a reversible manner, with IC 50 values in micromolar to submicromolar range (SI = 7‐400).…”
Section: Discovery and Development Of Mao‐b Inhibitors (2015‐2018)mentioning
confidence: 99%
See 1 more Smart Citation
“…In another study on benzofurans, Delogu et al designed a library of 2‐phenylbenzofuran derivatives ( 9a ‐ l ) by introducing a bromine substituent in the 2‐phenyl ring and a methyl group at the positions 5 to 7 in the benzofuran moiety (Figure ). Most of compounds preferentially inhibited hMAO‐B in a reversible manner, with IC 50 values in micromolar to submicromolar range (SI = 7‐400).…”
Section: Discovery and Development Of Mao‐b Inhibitors (2015‐2018)mentioning
confidence: 99%
“…The results demonstrated that the compounds exhibited moderate to good MAO-B inhibitory activity in the micromolar to submicromolar range with reversible and competitive modeF I G U R E 1 6 2-Arylidenebenzofuran-3(2H)-ones (8a-t) 153. hMAO, human monoamine oxidase; SI, selectivity index F I G U R E 1 7 2-Arylbenzofurans (9a-l) 154. hMAO, human monoamine oxidase; SI, selectivity index of inhibition.…”
mentioning
confidence: 99%
“…In our recent studies, we reported that 2-phenylbenzofuran derivatives display promising enzymatic inhibition properties against BChE [ 8 , 9 , 10 ] and monoamine oxidase (MAO) [ 11 , 12 , 13 ] enzymes. BChE plays a key role in the progression of Alzheimer’s disease (AD), a neurodegenerative disorder.…”
Section: Introductionmentioning
confidence: 99%
“…2 They also display pharmacological properties such as selective inhibitors of the butyrylcholinesterase enzyme (BChE) for Alzheimer's disease, 3 stimulation of neurite outgrowth of NGF-mediated PC12-cells, 4 streptococcus mutans sortase A, 5 and monoamine oxidase (MAO). 6 They are also used as building blocks for the synthesis of biologically active natural products and functional materials. 7 Among these, dihydrodibenzofuranone scaffolds were also isolated in nature ( Figure 1) and they exhibited broad biological activities.…”
Section: Introductionmentioning
confidence: 99%